ASSESSMENT OF THE RESISTANCE PROFILE OF Escherichia coli TO ANTIBIOTICS FROM AGRICULTURAL MICROBASIN LOCATED IN THE NORTHWEST OF THE STATE OF RIO GRANDE DO SUL, BRAZIL - Flach, Kauane; Rosa, Genesio Mario da; Bones, Ubiratan Alegransi; Soriani, Hilda Hildebrand (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2024)
Antimicrobial resistance acquired by bacteria is a central topic in discussions about the environment and emerging waterborne diseases. Therefore, the objective of this study was to determine the in vitro bacterial sensitivity, specifically of Escherichia coli (E. coli) strains previously isolated from Lajeado Pardo, located in the municipality of Frederico Westphalen, in the northwest region of Rio Grande do Sul state, Brazil. Five antimicrobials were tested using the Antimicrobial Sensitivity Test (AST) on isolated bacteria samples and evaluated according to their resistance (R) and sensitivity (S) profiles: ampicillin (AMP), amoxicillin-clavulanate (AMC), gentamicin (GEN), chloramphenicol (CHLO), and ciprofloxacin (CIP). The analysis of the selective isolation media (LSB, Colilert, and EC) showed statistically significant differences among them (p<0.05). Therefore, it can be inferred that the selective medium for bacterial isolation influenced the AST results. The AST revealed that out of the 12 tested bacterial strains, none showed the same behavior towards the antibiotics. AMP had the highest resistance rate (100.0%), followed by AMC (67.0%), CIP (50.0%), CHLO (50.0%), and GEN (42.0%). GEN proved to be the efficient drug for treatment and can be initially classified as satisfactory monotherapy. Out of the total n=12 samples from the four sectors, 83.33% (n=10) showed resistance to multiple drugs. The high rate of multidrug-resistant E. coli suggests a potential risk to public health when using untreated raw water.